Economic Growth and Total Factor Productivity in Niger - Nachega, Jean-Claude (IMF Working Papers; Working Paper, 2006)
This paper investigates empirically the sources of aggregate output growth and the determinants of total factor productivity (TFP) in Niger between 1963 and 2003. A growth accounting analysis indicates that the erosion in output per capita over the sample period is due to the negative growth of both TFP and physical capital per capita. Sound macroeconomic policies, supported by official development assistance and structural reforms, are found to be key to raising TFP growth.